ChemInform Abstract: Construction of 1‐Naphthols via Benzannulation Based on the Reaction of Aryl tert‐Butyl Ynol Ethers with Ynamides or Ynol Ethers. Issue 9 (February 2016) - Bai, Yihui; Yin, Jing; Liu, Zhicheng; Zhu, Gangguo
Abstract: A new version of benzannulation featuring the use of aromatic tert‐butyl ynol ethers (I) as convenient precursors for arylketenes is developed.